Fight Club: uma leitura política do capitalismo tardio na obra de Chuck Palahniuk - Vicentim, Fabiana (Universidade Federal de São Carlos, 2021)
The overall purpose of this dissertation is a political literary interpretation of the work Fight Club, that is, the narrative as a “symbolic social act”, and this perspective justifies the choice of cultural critic Fredric Jameson, as he proposes a dialectical reading that contemplates the social panorama, in addition to having a broad study on post-modernity and its concepts that are relevant to our study such as schizophrenia, consumerism, pastiche, fading of affection, among others.
Fight Club: a political reading about the late capitalism in Chuck Palahniuk's work
Keywords: Esquizofrenia; Pós-modernismo; Dialética; Fight Club; Schizophrenia; Postmodernism; Dialetic; LINGUISTICA, LETRAS E ARTES::LETRAS::TEORIA LITERARIA